Evaluation and control of absenteeism to Dentistry consultations in the school health program (Research, Society and Development, 2022)
The absences of dental consultations has motives that need to be studied together in order to intervene in order to reduce their rates. The study aims to measure absenteeism in scheduling and treatment among schoolchildren; evaluate the reasons for those responsible for not attending the scheduled appointment; and propose strategies for coping with absenteeism. A descriptive analysis of the results of the need assessment and the follow up of the curative actions was carried out. Semistructured interviews with the mothers were analyzed under the descriptive qualitative aspect. Of those who received the communication for scheduling only 32.98% made the markup. After the consultation, 75.52% attended. Of the students who attended the first consultation, 30.66% dropped out. In addition to non-marking, non-attendance and dropout, 85.31% of the students were absent from consultations. The mothers revealed that socio-cultural issues have a very important contribution and proposed ways of reducing absenteeism. How caregivers see health is crucial for deciding when to start treatment. Changing this paradigm is the key to achieving universal oral health based on health promotion, education and prevention.